2003
DOI: 10.1111/1468-2478.4701005
|View full text |Cite
|
Sign up to set email alerts
|

The Determinants of Aid Allocation by Regional Multilateral Development Banks and United Nations Agencies

Abstract: This paper examines which factors can explain the allocation of aid by four regional development banks as well as three United Nations agencies. The results suggest the following: most donors examined also exhibit a bias apparent in bilateral aid allocation in favor of less populous countries. Some of them also share another bias of bilateral donors who give more aid to their former colonies. However, the three United Nations agencies contravene a third bias of bilateral aid allocation and provide more aid to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
146
0
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 194 publications
(152 citation statements)
references
References 35 publications
2
146
0
4
Order By: Relevance
“…As Martens, et al (2002, p. 17) concludes, BMultilateral aid agencies may be somewhat shielded against direct political pressure from their member states.^Rodrik (1996) shows some aggregate evidence that supports the argument that Bmultilateral flows are less governed by political considerations than bilateral ones^ (Rodrik 1996, p. 176). Other macro-level empirical studies also produce results suggesting that multilateral agencies fund different countries and projects from bilateral ones, and that the former tend to target poorer countries and those with greater needs than those targeted by bilateral agencies (Maizels and Nissanke 1984;Frey and Schneider 1986;Tsoutsoplides 1991;Burnside and Dollar 2000;Neumayer 2003, Girod 2008.…”
Section: Introductionmentioning
confidence: 99%
“…As Martens, et al (2002, p. 17) concludes, BMultilateral aid agencies may be somewhat shielded against direct political pressure from their member states.^Rodrik (1996) shows some aggregate evidence that supports the argument that Bmultilateral flows are less governed by political considerations than bilateral ones^ (Rodrik 1996, p. 176). Other macro-level empirical studies also produce results suggesting that multilateral agencies fund different countries and projects from bilateral ones, and that the former tend to target poorer countries and those with greater needs than those targeted by bilateral agencies (Maizels and Nissanke 1984;Frey and Schneider 1986;Tsoutsoplides 1991;Burnside and Dollar 2000;Neumayer 2003, Girod 2008.…”
Section: Introductionmentioning
confidence: 99%
“…not climate funds such as the GCF or the Adaptation Fund). These organisations are more likely to argue from a developed country perspective given their donor-driven decision-making processes (see Gupta 1995;Kilby 2006;Neumayer 2003). The interviews were essential for two reasons.…”
Section: Methodsmentioning
confidence: 99%
“…Many studies have examined what factors -including country characteristicsthat de facto correlate with the allocation of aid across countries and country categories (Alesina and Dollar, 2000;Neumayer, 2003;Berthelemy, 2006;Dieleman et al, 2014). However, surprisingly few studies have examined the potential distributional implications of a wide range of aid allocation criteria, including the consequences for countries and country categories of using various criteria to a greater extent than today (Llavador and Roemer, 2001;Collier and Dollar, 2002;McGillivray, 2004;Guillaumont, 2008;Guillaumont et al, 2015).…”
Section: Transitions and Challengesmentioning
confidence: 99%
“…It has been suggested that per capita development assistance tend to decrease with population size or increase and then decrease (Alesina and Dollar, 2000;Neumayer, 2003;Salois, 2012). This may be explained by perceptions about the correlation between population size and other factors, such as economies of scale, resilience to shocks and effectiveness.…”
Section: Population Sizementioning
confidence: 99%